Arabic Illocutionary Speech Acts On Twitter With The Theme Of Love/ Tindak Tutur Ilokusi Bahasa Arab Pada Twitter Bertema Cinta - Nadya Amri Fauzie; Kholisin Kholisin (Ijaz Arabi Journal of Arabic Learning, 2023)
The study of pragmatics in understanding language and context involves elements of speech acts—the communication process between the speaker (speaker) and spoken (speech partner). The speech act is an approach to understanding meaning involving elocutionary, illocutionary, and perlocutionary elements in socio-psychological aspects. This study examines illocutionary speech acts on Twitter with the theme of love in the @1Naight account. This study used the descriptive qualitative method. The study is focused on describing the types and meanings of illocutionary speech acts in the Twitter account @1Naight. The data collection technique uses documentation by taking screenshots and writing uploaded tweets. Data analysis was carried out by writing and translating tweets, classifying them according to the type of speech and its function, and ending the data presentation process by describing the types and illocutionary meanings of each tweet studied. The results of this study are exposure to illocutionary speech act data, which includes powerful speech which serves to emphasize, directive speech that helps to suggest, command, plead, prohibit, and advise, and expressive vocabulary to express longing, gratitude, disappointment, hope, and regret.